Estimating Water Demand and Plant Evapotranspiration Using the Cropwat App - Moh. Syahrul Munir; Marcus dos Santos Soares; Abdul Jalil (Universitas Muhammadiyah Jember, 2022)
Water management is very important for plants and good water management can increase the productivity of rice, corn and soybeans, hereinafter referred to as PAJALE. This paper aims to estimate the water requirements of PAJALE plants using the cropwatt model. The results of the analysis show that each plant has different water requirements in each growth phase which was analyzed using cropwatt application throughout the year with medium textured soil types. Rice, corn and soybeans are the main food commodities in Indonesia. Corn and soybeans are generally planted after rice in irrigated and rainfed rice fields, making them susceptible to drought. Therefore, information using cropwatt applications, especially rainfall, temperature, Air humidity and solar radiation are very important in determining the time of planting and the right water requirements for plants. The purpose of the study was to determine the planting time and water requirements of rice, corn and soybeans, based on the results of cropwatt 8.0 analysis, and to compile a time map of Indonesian food crops so that the risk of production failure due to drought can be avoided.